Bahasa Gaul Dalam Kanal YouTube Bocah-Bocah Kosong: Kajian Sosiolinguistik - Bella Rahmania Putri Arisqi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe the forms of slang language varieties used in the YouTube channel "Bocah-Bocah Kosong" (BBK) and describe the language functions of the use of these slang language varieties in the communication process of the characters. The problems studied in this study are: (1) What are the forms of slang language varieties that appear in the YouTube channel Bocah-Bocah Kosong? (2) What are the language functions of the use of these slang language varieties in communication interactions on the channel? This study uses a descriptive qualitative approach with sociolinguistic studies. The research data are in the form of speech segments of characters in the YouTube video BBK that contain slang elements. Data collection techniques are carried out through free listening and note-taking techniques (documentation). Data analysis is carried out using an interactive model that includes data reduction, data presentation, and drawing conclusions. The results of the study show that the dominant forms of slang language varieties used in the YouTube channel Bocah-Bocah Kosong include acronyms (such as bucin, ojol, caper, mager), abbreviation (such as FYP, VT, DM, OTW), and clippings (such as bro and si). The use of slang fulfills various language functions according to Jakobson's theory, including the emotive function to express feelings of annoyance, admiration, or laziness (such as the words anjir, gokil, mager); the referential function to provide information related to a particular context; the conative function as an invitation; the phatic function to maintain social contact; and the metalingual function to explain certain slang terms so that they are understood by the interlocutor.
:: Finalisasi Repositori File 5 Juni 2026_Kurnadi
Keywords: Keywords: Slang; form of slang; slang Function; Bocah-Bocah Kosong (BBK).